Solvent extraction of copper enhanced by mixing cavities in micromixer - Sheik, Abdul Rauf; Kulkarni, Amol A.; Sanjay, Kali (Solvent Extraction Research and Development-Japan, 2021)
A Y micromixer with a macroscopic mixing cavity at the inlet junction was developed. The effects of the mixing cavity on the improvement of extraction of copper by LIX 841 were investigated. The investigated parameters and their ranges were: overall flow rate: 10 - 200 mL/min; microchannel size: 0.5 - 1 mm and mixing cavity diameter: 5 - 20 mm. Extraction efficiency, volumetric mass transfer coefficient, kinetics and pressure drop were investigated. The extraction efficiency and the volumetric mass transfer coefficient in the cavity micromixer were significantly higher than the Y micromixer. The volumetric mass transfer coefficient ranged between 1 - 93 s(-1), and the pressure drop between 50 - 500 kPa. The residence time required in the micromixers was two orders of magnitude lesser than that of an agitated batch reactor.